Psychological Motivations and Compulsive Buying: A Study of Consumers in Delhi - Singh, Shamsher; Tak, Preeti (Indian Journal of Marketing, 2013)
Compulsive buying behavior is an important area of research in consumer behavior research. The importance of studying this behavior lies in its nature as a negative aspect of consumer behavior. Negative aspects of consumer behavior are necessary to study since they may provide guidelines to policy makers to combat and reduce their impact. Such studies can also contribute to the society’s well being. The study examines the psychological motivations that lead to consumers’ compulsive buying behavior. Responses of 200 respondents from Delhi were collected by using a structured questionnaire. Convenience sampling was used to reach out to the respondents. Both primary and secondary sources were used to achieve the objectives of the study. ANOVA, factor analysis, and correlation analysis were applied on the collected data to draw significant results. The present study confirms that consumers are strongly influenced by their role models and indulged in compulsive buying behaviour. Individuals who are high in public self-consciousness are quite aware about their public image and use luxury goods to enhance their stature in the society. Materialistic individuals often relate possessions of goods to happiness and thus indulge in compulsive buying behavior. It was also found that there is no relationship between gender and compulsive buying.